The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1037/0096-1523.34.2.460
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual learning of noise vocoded words: Effects of feedback and lexicality.

Abstract: Speech comprehension is resistant to acoustic distortion in the input, reflecting listeners' ability to adjust perceptual processes to match the speech input. This adjustment is reflected in improved comprehension of distorted speech with experience. For noise vocoding, a manipulation that removes spectral detail from speech, listeners' word report showed a significantly greater improvement over trials for listeners that heard clear speech presentations before rather than after hearing distorted speech (clear-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
156
3
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 136 publications
(175 citation statements)
references
References 52 publications
15
156
3
1
Order By: Relevance
“…Previous behavioral studies have shown that the provision of relevant prior knowledge enhances both immediate perceptual clarity (1,29,35,45,46) and perceptual learning of degraded speech (6,14,(16)(17)(18). However, our work goes beyond these behavioral studies by identifying a common neural signal (reductions in the STG response) that is associated with both these effects.…”
Section: Common Mechanisms For Prior Knowledge and Perceptual Learningcontrasting
confidence: 40%
See 3 more Smart Citations
“…Previous behavioral studies have shown that the provision of relevant prior knowledge enhances both immediate perceptual clarity (1,29,35,45,46) and perceptual learning of degraded speech (6,14,(16)(17)(18). However, our work goes beyond these behavioral studies by identifying a common neural signal (reductions in the STG response) that is associated with both these effects.…”
Section: Common Mechanisms For Prior Knowledge and Perceptual Learningcontrasting
confidence: 40%
“…As described in SI Discussion, this account provides a neural implementation of "attentional weighting" theories of perceptual learning (5); with learning arising from Hebbian weight updates that minimize prediction errors when degraded speech matches prior predictions. This account therefore explains why perceptual learning of vocoded speech is enhanced when the content of degraded speech is predicted accurately (6,18); these trials lead to learning by allowing listeners to attend more appropriately to informative sensory features in degraded speech (5,7,62,63).…”
Section: A Predictive Coding Account Of Speech Perception and Perceptualmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a recent follow-up study modified this conclusion (Hervais-Adelman, Davis, Johnsrude, & Carlyon, 2008). Hervais-Adelman et al hypothesized that listeners in their previous study might have failed to learn from sentences made up of nonwords because such stimuli could be quite difficult to keep in memory, preventing perceptual learning processes from operating on them.…”
Section: I3 Perceptual Learning For Degraded Speech Inputmentioning
confidence: 71%